2023
DOI: 10.29333/ejeph/12446
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature and humidity on mortality in acute medical admissions

Abstract: The full effects of meteorological variables on mortality have not yet been elucidated. This study's aim was to investigate whether 30-day in-hospital mortality in emergency hospital admissions for non-respiratory diseases were sensitive to the effects of humidity and ambient temperature on the day of admission. We studied all emergency medical admissions to St. James's Hospital, Dublin, during 2002Dublin, during -2018 and investigated temperature and humidity on day of admission. We employed multivariable lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Braga et al found similar relative risks and lag-response relationships for heat effect on myocardial infarctions, cardiovascular disease, pneumonia, and overall daily deaths in eight cold cities in the U.S., including New Haven, CT [14]. Previous studies have also shown some heterogeneity in the effect of RH on temperature-related mortality, but most existing literature has suggested that humidity has a negligible effect on temperature mortality burdens, which is consistent with our results [24][25][26][27].…”
Section: Plos Climatesupporting
confidence: 91%
See 1 more Smart Citation
“…Braga et al found similar relative risks and lag-response relationships for heat effect on myocardial infarctions, cardiovascular disease, pneumonia, and overall daily deaths in eight cold cities in the U.S., including New Haven, CT [14]. Previous studies have also shown some heterogeneity in the effect of RH on temperature-related mortality, but most existing literature has suggested that humidity has a negligible effect on temperature mortality burdens, which is consistent with our results [24][25][26][27].…”
Section: Plos Climatesupporting
confidence: 91%
“…For this data, the daily mean saturation vapor pressure was calculated from the daily mean temperature, and mean RH was calculated as the mean water vapor pressure divided by the mean saturation vapor pressure. In our models, we applied a natural cubic spline with 3 degrees of freedom for each measure of RH [24][25][26][27]. All humidity calculations were done using the 'humidity' package in R [28].…”
Section: Competing Interestsmentioning
confidence: 99%
“…Recent concern in respect to Bangladesh arises is the heat effect on human and plants due to ambient temperature. Although unhealthy temperatures, extreme temperatures, and even moderately high or low temperatures can have an impact 2024 -European Journal of Chemistry -CC BY NC -DOI: 10.5155/eurjchem.15.1.79-86.2511 on death, the overall influence of humidity on mortality has not been epidemiologically demonstrated conclusively [7]. Additionally, in vulnerable plant species, these air pollutants can cause leaf damage, stomatal damage, early senescence, reduced photosynthetic activity, disturbed membrane permeability, and restricted growth and production.…”
Section: Introductionmentioning
confidence: 99%